1995
DOI: 10.1146/annurev.ge.29.120195.000441
|View full text |Cite
|
Sign up to set email alerts
|

Dna Repair in Humans

Abstract: KEY WORDS: re pair enzy me s, transc ri pti on-repai r coupli ng, cell cycle and re pai r, ce llular re spo nse to damage, damage and canc er, re pair and chemotherapy ABSTRACT DNA repair is an important molecular defense system against agents that cause cancer, degenerative diseases, and aging. Several repair systems in humans protect the genome by repairing modified bases, DNA adducts, cross links, and double strand breaks. These repair systems, base excision, nucleotide excision, and recombination, are inti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
62
0
4

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(66 citation statements)
references
References 101 publications
(81 reference statements)
0
62
0
4
Order By: Relevance
“…11 APE1 also acts as a 3 0 -phosphodiesterase to initiate repair of single strand breaks, 9,12,13 damage that may result from direct attack and fragmentation of deoxyribose residues in DNA by free radicals. 9,[14][15][16] By hydrolyzing 3 0 -blocking fragments from oxidized DNA, APE1 produces normal 3 0 -hydroxyl nucleotide termini that are necessary for DNA repair synthesis and ligation at single-or double-strand breaks. 9,17 A common APE1 polymorphism, a TfiG transversion (Asp 148 Glu), was shown to have 94% of the endonuclease activity relative to the Asp allele, and 21% less binding activity (K d , 20.3 6 3.4 versus 25.8 6 12.2 nM in Asp allele).…”
mentioning
confidence: 99%
“…11 APE1 also acts as a 3 0 -phosphodiesterase to initiate repair of single strand breaks, 9,12,13 damage that may result from direct attack and fragmentation of deoxyribose residues in DNA by free radicals. 9,[14][15][16] By hydrolyzing 3 0 -blocking fragments from oxidized DNA, APE1 produces normal 3 0 -hydroxyl nucleotide termini that are necessary for DNA repair synthesis and ligation at single-or double-strand breaks. 9,17 A common APE1 polymorphism, a TfiG transversion (Asp 148 Glu), was shown to have 94% of the endonuclease activity relative to the Asp allele, and 21% less binding activity (K d , 20.3 6 3.4 versus 25.8 6 12.2 nM in Asp allele).…”
mentioning
confidence: 99%
“…A host of complex cellular DNA repair mechanisms have evolved to counteract the deleterious effects of DNA damage in humans (7). In addition to the existence of several detoxification systems, delays at specific stages of the cell cycle occur after DNA damage, most likely for the efficient and optimal removal of DNA lesions from the cellular genome before cell division (8,9).…”
mentioning
confidence: 99%
“…These results are in agreement with a previous study showing no significant association between mRNA levels of wild-type and polymorphic types in RRM1 G2464A alone (P ¼ 0.301), or a combination of several types of RRM1, including RRM1 A2455G, in 62 human cancer cell lines were used, including six lung cancer cell lines. 28 In the same study, the RRM1 G2464A polymorphism demonstrated an association with gemcitabine sensitivity, 30 while together with the A2455G polymorphism was associated with neutropenia after gemcitabine treatment in breast cancer patients. 29 Therefore, further functional studies evaluating coexpressing genes, as well as prospective clinical trial for its application as a predictive biomarker are needed.…”
Section: Expression Of Drug-related Genes In Nsclcmentioning
confidence: 85%
“…Drug resistance occurs mostly because of detoxification or efficient repair of damaged DNA by the members of the nucleotide excision repair system, including ERCC1. 30 In vitro studies demonstrated that upregulation of ERCC1 is associated with cisplatin resistance 31 and clinical studies demonstrated that response and survival of patients with advanced NSCLC were improved in the presence of low ERCC1 expression. 32,33 A low ERCC1 expression was also related to better outcome to adjuvant cisplatin-based chemotherapy in patients with completely resected NSCLC.…”
Section: Introductionmentioning
confidence: 99%